Efeitos do treinamento muscular inspiratório e da cinesioterapia respiratória na capacidade de exercício, sincronia tóraco-abdominal e na função muscular respiratória em pacientes com DPOC - Basso, Renata Pedrolongo (Universidade Federal de São Carlos, 2013)
The present thesis has a result three studies in which the aims were: Study I To propose an assessment method of inspiratory muscle endurance (IME) using the traditional manuvacuometry and the PowerBreathe® device. Moreover, the aim was to verify its viability in patients with Chronic Obstructive Pulmonary Disease (COPD) and healthy. Study II To compare the inspiratory muscle training (IMT) and respiratory exercise (RE) effects associated with physical training (PT) regarding to strength and endurance gain of inspiratory muscles, thoracoabdominal mobility, physical exercise capacity and dyspnea during physical efforts in patients with COPD. In additional, it was to verify if there is a relation of changing gained post training among these variables. Study III To verify if the IMT and/or RE modality associated to PT can provide changes in inspiratory muscle strength, in thoracoabdominal asynchronism and dyspnea at rest and during unsupported upper limb (UL) exercises. Additionally, it was to verify if there is a difference between these both technics modalities. The total sample was composed of 19 healthy subjects and 25 patients with COPD; 13 in the GPT+IMT group and 12 in the GPT+RE. All subjects were assessed before and after training by spirometry; measures of maximum inspiratory (MIP) and expiratory pressures (MEP), IME test, in which was determined the sustained maximum inspiratory pressure (SMIP) and the limit time (Tlim), cirtometry, sixminute walking test (6MWT) and treadmill exercise test (TT). Moreover, reported the modified Medical Research Council (mMRC) and the assessment of respiratory inductance plethysmography (RIP). The IME test was well tolerated. The MIP, MIP %pred, SMIP and SMIP/MIP values were significant lower (p<0.05) in patient with COPD. There was no significant difference between COPD and healthy subjects regarding to Tlim. In the GPT+IMT the MIP, SMIP, abdominal mobility values were significant higher (p<0.05); and, the dyspnea was significantly lower in the 6MWTpeak, TT and mMRC post treatment. However, in both groups there was a significant rise of MIP and SMIP, thoracoabdominal mobility, 6MWD and inclination at TT; and, fall of dyspnea at 6MWTpeak (p<0.05). Only in the GPT+IMT there was a decreased of thoracoabdominal asynchronism at rest and during UL exercises. The PowerBreathe® device associated with the manovacuometry makes acceptable the IME test in patients with COPD and healthy subjects, specially using the incremental load. Both technics increased the exercise capacity and decrease dyspnea at efforts clinically significant. Although, due to the training specificity, only the IMT group was able to improve the inspiratory strength and endurance, which results in a pronounced reduction of dyspnea and thoracoabdominal asynchronism at rest and during UL exercises.
Keywords: Fisioterapia; DPOC (Doença Pulmonar Obstrutiva Crônica); Músculos respiratórios; Exercícios respiratórios; Dispneia; COPD; Respiratory muscle; Dyspnea; Physical therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL